If f : C → C is defined by


If $f: C \rightarrow C$ is defined by $f(x)=(x-2)^{3}$, write $f^{-1}(-1)$.


Let $f^{-1}(-1)=x$                      $\ldots(1)$

$\Rightarrow f(x)=-1$


$\Rightarrow x-2=-1$ or $-\omega$ or $-\omega^{2}$      (as the roots of $(-1)^{\frac{1}{3}}$ are $-1,-\omega$ and $-\omega^{2}$, where $\left.\omega=\frac{1+i \sqrt{3}}{2}\right)$

$\Rightarrow x=-1+2$ or $2-\omega$ or $2-\omega^{2}=1,2-\omega, 2-\omega$

$\Rightarrow f^{-1}(-1)=\left\{1,2-\omega, 2-\omega^{2}\right\} \quad[$ from $(1)]$

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now